Niche construction as a theoretical tool in the ethnographic analysis from a naturalistic perspective - Crivos, Marta Alicia (2019)
In this work, we intend to move discussion forward on the heuristic role of the concept of niche construction for the review of the human/environment dichotomy by considering the interaction between biotic and abiotic components inspecific environments. We will examine an ethnographic case study which explores the perception of the landscape and its use by different human groups (Mbyá-Guaraní and descendants of European colonos) that inhabit a territory withcommon biophysical features: The Paranaense forest in Northeastern Argentina. According to these narratives, the consideration of the monte is closely related to the modes of interaction with the natural environment resulting from theirdaily subsistence practices. This comparative study shows how the monte has been differentially built and valued in the course of this interaction.